Selective Support for the Development of Regional Vocational Education Services: the Russian Experience - Linar G. Akhmetov; Natalia A. Khramova; Anna V. Sychenkova; Alexey D. Chudnovskiy; Natalya B. Pugacheva; Andrey A. Pavlushin; Marina V. Varlamova; Victoriya A. Khilsher (International Review of Management and Marketing, 2016)
The paper relevance is reasoned by the optimization of management of regional vocational educational services. Russian regions differ from each other very much by social and economic indicators, as well as the climatic and geographical conditions. The Russian government initiated a number of reforms aimed at ensuring of equal access to vocational educational services and infrastructure across the country. One of the important components of such reforms is a targeted selective support for the development of regional vocational educational services. The paper aims to find out the specifics of selective support for the development of regional vocational educational services. The leading method is the method of action research (AR), providing new information on the management of vocational education in the region and proposing methods for development of regional vocational educational services. The paper presents a selective mechanism to support the development of regional vocational educational services. Principles (consensus and initiative) are defined and methods (legal-regulatory, financial-economic, socio-political, information-communication, private- entrepreneurial, civil- initiative) are identified of selective support for the development of regional vocational educational services. It is found that the selective support for the development of regional vocational educational services is a component of the socio-economic development of the region and the imperative to improve the quality of life of the population. Article Submissions can be useful for research and teaching staff of vocational education, specialists of education authorities and regional authorities.